Tuning the Dispersibility of Carbon Nanostructures from Organophilic to Hydrophilic: Towards the Preparation of New Multipurpose Carbon‐Based Hybrids. Issue 38 (9th August 2013) - Georgakilas, Vasilios; Kouloumpis, Antonios; Gournis, Dimitrios; Bourlinos, Athanasios; Trapalis, Christos; Zboril, Radek
Abstract The hydroxyphenyl derivatives of carbon nanostructures (graphene and carbon nanotubes) can be easily transformed into highly organophilic or hydrophilic derivatives by using the ionic interactions between the phenolic groups and oleylamine or tetramethylammonium hydroxide, respectively. The products were finely dispersed in homo‐polymers or block co‐polymers to create homogeneous carbon‐based nanocomposites and were used as nanocarriers for the dispersion and protection of strongly hydrophobic compounds, such as large aromatic chromophores or anticancer drugs in aqueous solutions.